4x+3y = 6 3y = -4x+6 y = -4/3x+2 in slope intercept form
4x + 6 = 6x - 12-4x -4x6 = 2x - 12+12 +1218 = 2xx=9
the solution for the inequality 4x + 2 - 6x < -1 was x < 3/2
x3 + 6x2 - 4x - 24 = (x + 6)(x2 - 4) = (x + 6)(x + 2)(x - 2)
Assume the expression is:4/(x + 2) + 6/(x + 5)Simplify this expression by combining the expressions altogether. Let's go step by step.Step 1: Determine the LCD of the expression.The LCD of the expression is (x + 2)(x + 5). Multiply the top and bottom of each fractional expression by whatever factor the denominator is missing!4/(x + 2) * (x + 5)/(x + 5) + 6/(x + 5) * (x + 2)/(x + 2)Step 2: Combine the expression and simplify.(4(x + 5) + 6(x + 2))/((x + 2)(x + 5))= (4x + 20 + 6x + 12)/((x + 2)(x + 5))= (10x + 32)/((x + 2)(x + 5))
The expression 9+5 is equivalent.
It is an expression that can be simplified to 5y+2x-6
x2 + 4x + 6 can not be factored. If you want, you can reduce it to an expression with a single x term by comleting the square: x2 + 4x + 6 = x2 + 4x + 4 + 2 = (x + 2)2 + 2
45
4x**3-x**2*24x+6 is an expression, it has no answer however it factors to: (4x-1)(x**2-6)
The expression is 33.
If you mean -6+4x-5 then the given expression can be simplified to 4x-11 and the unknown variable is x
17 + 6 + m
Yes, -6+x is the same as x-6.
(6-4x)(x-2)+3x =6x-12-4x+8x+3x =5x-4
8x + 5z - 4x + 3z + 6 = 8x - 4x + 5z + 3z - 6 = 4x + 8z - 6
55